How Metabolomics Provides Novel Insights on Celiac Disease and Gluten-Free Diet: A Narrative Review - Vacca, Mirco; Porrelli, Annalisa; Calabrese, Francesco Maria; Lippolis, Tamara; Iacobellis, Ilaria; Celano, Giuseppe; Pinto, Daniela; Russo, Francesco; Giannelli, Gianluigi; De Angelis, Maria (Frontiers in Microbiology, 2022)
Celiac disease (CD) is an inflammatory autoimmune disorder triggered by the ingestion of gluten from wheats and other cereals. Nowadays, its positive diagnosis is based on invasive approaches such as the histological examination of intestinal biopsies and positive serology screening of antibodies. After proven diagnosis, the only admissible treatment for CD individuals is a strict life-long adherence to gluten-free diet (GFD), even though it is not a conclusive therapy. Through different mechanisms and etiology, both CD and GFD have a great impact on gut microbiota, leading to a dysbiosis. The microbiota reflects dysbiosis through an altered production of specific metabolites. The current literature reported some suggestions about the possible use of specific metabolites, detected by meta-omics analyses, as potential biomarkers for a CD non-invasive diagnosis. We conducted a narrative dissertation of original research articles published in the last twenty years with the purpose of highlighting insights about metabolomics application for CD study. Applying a systematic search, it emerged that the metabolomic signature did not follow a common line among the studies and, in addition, it is still poorly investigated.